2001
DOI: 10.1099/0022-1317-82-11-2821
|View full text |Cite
|
Sign up to set email alerts
|

Genome organization of the densovirus from Bombyx mori (BmDNV-1) and enzyme activity of its capsid

Abstract: Bombyx mori densovirus (BmDNV-1), on the basis of the previously reported genome sequence, constitutes by itself a separate genus (Iteravirus) within the Densovirinae subfamily of parvoviruses. Inconsistencies in the genome organization, however, necessitated its reassessment. The genome sequence of new clones was determined and resulted in a completely different genome organization. The corrected sequence also contained conserved sequence motifs found in other parvoviruses. Some amino acids in the highly cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
59
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 19 publications
0
59
0
Order By: Relevance
“…The activity of PLA 2 is critical for the efficient transfer of the viral genome from late endosomes to the nucleus to initiate replication and thus for parvovirus infectivity (Zadori et al, 2001). This enzyme activity of the capsid was also demonstrated for BmDNV-1 (Li et al, 2001) and CeDNV (Fédière et al, 2002). Interestingly, this motif appears to be less conserved in the MpDNV structural proteins (30-36 % identity within a stretch of 39 aa with the other DNVs).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The activity of PLA 2 is critical for the efficient transfer of the viral genome from late endosomes to the nucleus to initiate replication and thus for parvovirus infectivity (Zadori et al, 2001). This enzyme activity of the capsid was also demonstrated for BmDNV-1 (Li et al, 2001) and CeDNV (Fédière et al, 2002). Interestingly, this motif appears to be less conserved in the MpDNV structural proteins (30-36 % identity within a stretch of 39 aa with the other DNVs).…”
Section: Discussionmentioning
confidence: 96%
“…The function of the second region, the so-called PGY motif, highly conserved (70-98 % identity within a stretch of 39 aa in VP1) among vertebrate parvoviruses and DNVs (Dumas et al, 1992), was elucidated recently. Zadori et al (2001) showed that this region was part of the catalytic site of secretory phospholipase A 2 (PLA 2 ). The activity of PLA 2 is critical for the efficient transfer of the viral genome from late endosomes to the nucleus to initiate replication and thus for parvovirus infectivity (Zadori et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PLA2 activity is thought to be required between the stage of perinuclear accumulation of virions and the stage of early gene expression (22,39,86). Injection of VP1-specific antibodies into the cytoplasm of cells prior to inoculation with CPV prevented infection, suggesting that this domain is accessible to antibody recognition within the cytoplasm (69).…”
mentioning
confidence: 99%
“…The parvovirus family has been divided into two subfamilies, the Parvovirinae, which infect vertebrates, and the Densovirinae, which infect invertebrates. Bombyx mori densovirus 1 (BmDNV-1) belongs to the Densovirinae subfamily (genus Iteravirus) (17) and causes potentially lethal flacherie disease in silkworms (28), thereby posing a major threat to silk production. So far, only CeDNV (from Casphalia extranea), DpDNV (from Dendrolimus punctatus), and BmDNV-1 belong to the genus Iteravirus, whereas BmDNV-2 and -3 have a bipartite genome with a total length of about 12.5 kb and have been excluded from the Parvoviridae and reassigned to a new family (Bidnaviridae) (31).…”
mentioning
confidence: 99%